2009 2nd IEEE International Conference on Computer Science and Information Technology 2009
DOI: 10.1109/iccsit.2009.5234433
|View full text |Cite
|
Sign up to set email alerts
|

Integrated project management of sustainable water storage and seawater intrusion prevention in a costal city

Abstract: This work addressed the integrated project management of water resources in a costal city, Haihou City in China. Based on investigation of renewable water resources distribution, an underground water storage project was carried out for water safety utility and seawater intrusion prevention in the new planned city area. Methods for surface water reuse and seawater intrusion prevention were integrated to produce comprehensive program management in the project. River water was transported to inner lakes through c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The monitoring of the piezometric head and measuring of the electrical conductivity indicated that the recharge dam was effective and contributed positively toward improving the groundwater quality in the coastal zone. Yuansheng and Zhaohui [66] introduced the artificial recharge of water as an efficient measure to control SWI and elevate the groundwater levels. By transporting river water to inner lakes through a pre-constructed canal, they developed an integrated methodology for future sustainability of the flow system in the coastal city of Haihou, China.…”
Section: Artificial Rechargementioning
confidence: 99%
“…The monitoring of the piezometric head and measuring of the electrical conductivity indicated that the recharge dam was effective and contributed positively toward improving the groundwater quality in the coastal zone. Yuansheng and Zhaohui [66] introduced the artificial recharge of water as an efficient measure to control SWI and elevate the groundwater levels. By transporting river water to inner lakes through a pre-constructed canal, they developed an integrated methodology for future sustainability of the flow system in the coastal city of Haihou, China.…”
Section: Artificial Rechargementioning
confidence: 99%
“…There are about 15 methods which would be applicable for controlling intrusion of saltwater in various areas around the globe [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Details are summarized as follows: 1) Water diversion Details/Benefits: Use of excessive fresh water via open canal or tunnel for pushing saltwater and for diversion purposes.…”
Section: Literature Reviewmentioning
confidence: 99%